2003
DOI: 10.1046/j.1469-0691.2003.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Current strategies to avoid misdiagnosis of malaria

Abstract: Malaria remains the most important parasitic disease, and tens of thousands of cases are imported into non-endemic countries annually. However, any single institution may see only a very few cases-this is probably the reason why laboratory and clinical misdiagnosis may not be uncommon. In the laboratory, unfamiliarity with microscopic diagnosis may be the main reason, considering the large number of laboratory staff who provide on-call services, often without expert help at hand, as well as the difficulty in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 33 publications
1
73
0
1
Order By: Relevance
“…In resource-poor endemic settings, there may be problems related to equipment, expertise and workload, whereas in non-endemic settings in industrialised countries, there may be a lack of routine among the laboratory staff, resulting in low expertise [1]. In these circumstances, the use of malaria rapid diagnostic tests (MRDTs) can be valuable in the diagnosis of malaria [1,2]. MRDTs detect antigens specific to one or more of the Plasmodium species.…”
Section: Introductionmentioning
confidence: 99%
“…In resource-poor endemic settings, there may be problems related to equipment, expertise and workload, whereas in non-endemic settings in industrialised countries, there may be a lack of routine among the laboratory staff, resulting in low expertise [1]. In these circumstances, the use of malaria rapid diagnostic tests (MRDTs) can be valuable in the diagnosis of malaria [1,2]. MRDTs detect antigens specific to one or more of the Plasmodium species.…”
Section: Introductionmentioning
confidence: 99%
“…95% of the deaths due to malaria (33). The current standard for diagnosis is the microscopic examination of Giemsa-stained thick and thin blood smears (12,16,21,22,28). This procedure is time-consuming to prepare, read, and interpret the slides.…”
mentioning
confidence: 99%
“…This procedure is time-consuming to prepare, read, and interpret the slides. Previous studies have shown that even with experienced microscopists, misdiagnosis occurs, particularly in cases of mixed infection or low parasitemia (12,28). Immunochromatographic assays based on antigen detection have been developed but are also relatively insensitive in cases of low parasitemia (22,24,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, even experienced microscopists have been found to misdiagnose cases involving low parasitemia or mixed infections. [7][8][9] Moreover, morphological similarities between P. knowlesi and P. malariae often result in misdiagnosis. 10 Although RDTs are generally specific for detecting P. falciparum and P. vivax infections, they are non-specific for other malaria species.…”
Section: Introductionmentioning
confidence: 99%